Patient-practitioner interaction styles. (SAGE Publications Ltd, 2017)
Using a case study of sexually transmitted diseases in women, Dr. Adina Nack discusses patient-practitioner interaction styles. Sexually transmitted diseases, especially in women, carry a lot of stigma that can come from the medical professionals. Nack discusses moral surveillance style practitioners, biomedical style practitioners, and patient-centered style practitioners.